INNOVATIVE SYSTEM OF SOLAR PANELS CLEANING - Kamanova, Gulkhan; Shosaitov, Shavkat (Techscience uz - Topical Issues of Technical Sciences, 2025)
The article considers the issues of effective use of solar panels in winter due to automatic cleaning devices. The proposed device allows you to use solar energy in the maximum amount, regardless of weather conditions and season. This device can be used in the construction of new solar power plants, as well as in the modernization of existing ones. The development and modernization of solar energy will allow you to improve the economic aspect of the energy situation in our country in the future.